Team Games Tournament Cooperative Learning Model on the Understanding of Pancasila Values Students at Elementary School - Nova K. Kolway; Titus Gaite; Fransina M. B. Rahaor (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The use of less interactive learning models often triggers a low understanding of Pancasila values at the elementary school level. This study aims to examine the effect of the Team Games Tournament (TGT) cooperative learning model on the understanding of Pancasila values ​​in second-grade students at Elementary School 2 Ambon. Using a quasi-experimental design with a pretest-posttest control group design, this study involved 42 students divided into an experimental group (Grade IIA, n=21) and a control group (Grade IIB, n=21). Data was analyzed using descriptive statistics, prerequisite tests, and hypothesis testing through the independent sample t-test. The results showed that the implementation of the TGT model had a significant effect on student understanding, as evidenced by the Sig. (2-tailed) value of 0.012 < 0.05. The experimental group achieved a superior average understanding (mean = 89.05) compared to the control group (mean = 85.71) with an average difference of 16 points in favor of the treatment group. TGT works because it gets students involved by making them compete academically, interact with each other, and practice the values of cooperation and deliberation directly. These findings provide an innovative alternative for educators to strengthen the effectiveness of Pancasila Education through a social constructivist approach in elementary schools.